Thyroid FT4-to-TSH ratio in the first trimester is associated with gestational diabetes mellitus in women carrying male fetus: a prospective bi-center cohort study - Song, Shuoning; Zhang, Yuemei; Qiao, Xiaolin; Duo, Yanbei; Xu, Jiyu; Zhang, Jing; Chen, Yan; Nie, Xiaorui; Sun, Qiujin; Yang, Xianchun; Wang, Ailing; Lu, Zechun; et al. (Frontiers in Endocrinology, 2024)
Gestational diabetes mellitus (GDM) is one of the most common medical complications of pregnancy, which increases the risk of other pregnant complications and adverse perinatal outcomes. Thyroid dysfunction is closely with the risk of diabetes mellitus. However, the relationship between euthyroid function in early pregnancy and GDM is still controversial.This study was to find the relationship between thyroid function within normal range during early pregnancy as well as glucose and lipids metabolisms as well as the risk of subsequent GDM.A total of 1486 pregnant women were included in this prospective double-center cohort study. Free thyroxine (FT4), thyroid stimulating hormone (TSH) and antithyroid peroxidase antibodies (TPOAb) were tested during 6-12 weeks of gestation and oral glucose tolerance test (OGTT) was conducted during 24-28 weeks to screen GDM. Relative risks (RR) with 95% confidence intervals (CI) for subsequent risk of GDM by thyroid function quartiles were assessed adjusting for major risk factors.The incidence of GDM was 23.0% (342/1486). TSH, FT4 and the percentage of positive TPOAb were no significant difference between women with and without GDM, but FT4/TSH ratio was significantly higher in GDM group compared with NGT group [6.97(0.84,10.61) vs. 4.88(0.66,12.44), P=0.025)]. The linear trends of TC, TG, HDL-C, LDL-C, fasting glucose in the first trimester, insulin, C-peptide, HOMA-IR, fasting glucose during OGTT and incidence of GDM according to FT4/TSH ratio were all statistically significant. Further analysis based on fetal sex presented only the third quartile of FT4/TSH ratio in women carrying male fetus was associated with higher incidence of GDM statistically significant [RR (95% CI), 1.917 (1.143,3.216)], rather than in women carrying female fetus.Thyroid function even in normal range is closely related to glucose and lipids metabolisms during the first trimester. Unappropriated FT4/TSH ratio in the first trimester is an independent risk factor of GDM in women carrying male fetus.